Health Potential and Physicochemical Attributes after Minimal Processing and during Refrigerated Storage of Orange (Citrus sinensis L., Osbeck) - Van de Velde, Franco (2013)
Changes after minimal processing and during refrigerated storage for10 days at 3◦C of sweet oranges (cv. Valencia Late) were evaluated. Physicochemical and sensory attributes and health potential (ascorbic acid, total phenolics, and antioxidant capacity) were quantified. The minimal processing (in wedges and slices) did not cause significant changes in quality attributes. Ascorbic acid was retained by over 70% until day 10 of storage at 3◦C, total phenolics remained constant, and antioxidant capacity showed a significant decrease until day 5, and then remained constant. Sensory analysis indicated absence of surface dryness at day 10 and a moderate development of off-odors at day 7.